Informação polarimétrica PALSAR/ALOS aplicada à discriminação de espécies e estimação de parâmetros morfológicos de macrófitas - Sartori, Lauriana Rúbio [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
O propósito deste trabalho foi avaliar o potencial dos dados PALSAR polarimétricos para discriminar e mapear espécies de macrófitas (vegetação aquática) de uma área alagável da Amazônia, a planície de inundação do Lago Grande de Monte Alegre, no estado do Pará. A coleta de dados foi realizada quase simultaneamente à aquisição dos dados de radar. Três principais espécies de macrófitas foram encontradas na área: Paspalum repens (PR), Hymenachne amplexicaulis (HA) e Paspalum elephantipes (PE). Variáveis morfológicas foram medidas em campo e usadas para derivar outras variáveis tais como a biomassa. Atributos foram gerados a partir da matriz de covariância [C] extraída da imagem ALOS/PALSAR em modo SLC (single look complex). Os atributos polarimétricos foram analisados para as três espécies e identificados aqueles capazes de discriminar as espécies. Foram aplicadas as seguintes abordagens de classificação: baseada em regras, baseada em modelos de decomposição (Decomposições de Freeman-Durden e Cloude-Pottier), baseada em estatística (Classificação supervisionada baseada na distância Wishart) e híbrida (Classificador Wishart com classes de entrada baseadas na decomposição de Cloude-Pottier). Finalmente, a variável morfológica “volume da haste” foi modelada por regressão múltipla em função de alguns atributos polarimétricos. Os resultados sugerem que a imagem polarimétrica banda L possui potencial para discriminar as espécies de macrófitas, sendo os principais atributos para isso sigma zero HH ( ), sigma zero HV ( ) e sigma zero VV ( ), índice de estrutura da copa...

The purpose of this work was to evaluate the potential of fully polarimetric PALSAR data to discriminate and map macrophyte species in the Amazon floodplain, more specifically in the Monte Alegre Lake, in the state of Pará, Brazil. Fieldwork was carried out almost simultaneously to the radar acquisition. Three main species were found in the study area: Paspalum repens (PR), Hymenachne amplexicaulis (HA) and Paspalum elephantipes (PE). Macrophyte morphological variables were measured on the field and used to derive others variables, like the biomass. Attributes were calculated from the covariance matrix [C] derived from the SLC (single look complex) data. The polarimetric attributes were analyzed for the three species and it was identified that ones capable of discriminating them. The following classification approaches were applied: a rule-based classification, model-based classifications (Freeman-Durden and Cloude-Pottier), a statistical-based classification (supervised classification using Wishart distance measure) and a hybrid classification (Wishart classifier with the input classes based on the H/a plane). Finally, the morphological variable “stem volume” was modeled using multiple regression. The findings suggest that the fully polarimetric image has potential for discriminating plant species, being the main attributes sigma-nought HH ( ), sigma-nought HV ( ) and sigma-nought VV ( ), canopy structure index ( ), HH-VV polarimetric coherence ( ), helicity of the third scattering mechanism (τ ), orientation angle of the first scattering mechanism ( ) and scattering type phase of the first mechanism ( ); among the different classifications, only the supervised (Wishart) and the rule-based discriminated the species, with overall accuracy of 75,04% and 87,18%, respectively; the stem volume was modeled using the following attributes: biomass index ( ), volumetric scattering ... (Complete abstract click electronic access below)
Keywords: Cartografia; Classificação; Espécies de macrófitas; Planície de inundação da Amazônia; Radar polarimétrico; Dados PALSAR; Regressão linear múltipla; Macrophyte species; Amazon floodplain; Radar polarimetry; PALSAR data; Polarimetric decomposition; Classification; Multiple linear regression